Applications of Intelligent Control to Engineering Systems - Valavanis, Kimon P. (Intelligent Systems, Control, and Automation: Science and Engineering, 2009)
This book represents the work of top scientists in the field of intelligent control and its applications, prognostics, diagnostics, condition based maintenance and unmanned systems. The work presents an approach to solving engineering problems related to manufacturing, automation, and especially unmanned systems and describes recent advances in the disciplines mentioned above. The main goal of the book is to demonstrate how concepts and ideas from diverse disciplines are merged within a common framework applied to the solution of complex problems.